Draft genome sequence of Dethiosulfovibrio salsuginis DSM 21565(T) an anaerobic, slightly halophilic bacterium isolated from a Colombian saline spring - Díaz-Cárdenas, Carolina (Stand Genomic Sci, 2017)
A bacterium belonging to the phylum Synergistetes, genus Dethiosulfovibrio was isolated in 2007 from a saline spring in Colombia. Dethiosulfovibrio salsuginis USBA 82(T) (DSM 21565 (T) = KCTC 5659 (T) ) is a mesophilic, strictly anaerobic, slightly halophilic, Gram negative bacterium with a diderm cell envelope. The strain ferments peptides, amino acids and a few organic acids. Here we present the description of the complete genome sequencing and annotation of the type species Dethiosulfovibrio salsuginis USBA 82(T). The genome consisted of 2.68 Mbp with a 53.7% G + C. A total of 2609 genes were predicted and of those, 2543 were protein coding genes and 66 were RNA genes. We detected in USBA 82(T) genome six Synergistetes conserved signature indels (CSIs), specific for Jonquetella, Pyramidobacter and Dethiosulfovibrio. The genome of D. salsuginis contained, as expected, genes related to amino acid transport, amino acid metabolism and thiosulfate reduction. These genes represent the major gene groups of Synergistetes, related with their phenotypic traits, and interestingly, 11.8% of the genes in the genome belonged to the amino acid fermentation COG category. In addition, we identified in the genome some ammonification genes such as nitrate reductase genes. The presence of proline operon genes could be related to de novo synthesis of proline to protect the cell in response to high osmolarity. Our bioinformatics workflow included antiSMASH and BAGEL3 which allowed us to identify bacteriocins genes in the genome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi: 10.1186/s40793-017-0303-x) contains supplementary material, which is available to authorized users.